2021
DOI: 10.1016/j.ajic.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta-analysis of the accuracy of diagnostic tests for COVID-19

Abstract: Highlights RT-PCR followed by CT shows high sensitivity for detecting COVID-19. Immunological tests should use a combination of IgG and IgM. The genes E and RdRp present high analytical sensitivity to detect the virus. Assays for molecular diagnosis should employ 2-target systems. Studies of diagnostic tests for COVID-19 are of moderate methodological quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
441
5
18

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(482 citation statements)
references
References 36 publications
(99 reference statements)
18
441
5
18
Order By: Relevance
“…Furthermore, our rates of growth in prevalence of the virus were similar among symptomatic people and those without symptoms who would be largely ineligible for testing through the routine 'test and trace' programme. An additional limitation is that a nose and throat swab may have limited sensitivity (~70% to 80%) [7] to detect virus, but this should not affect trends in prevalence within or between rounds.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our rates of growth in prevalence of the virus were similar among symptomatic people and those without symptoms who would be largely ineligible for testing through the routine 'test and trace' programme. An additional limitation is that a nose and throat swab may have limited sensitivity (~70% to 80%) [7] to detect virus, but this should not affect trends in prevalence within or between rounds.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Primary clinical performance data Eight systematic reviews were identified, including one by health technology assessment bodies not listed as a peer-reviewed study, and the primary studies included in the analysis extracted. [6][7][8][9][21][22][23][24] The full list of studies in the FIND and EC databases was retrieved on 22 August 2020. Pubmed was searched on the same date.…”
Section: Resultsmentioning
confidence: 99%
“…To select the optimal pool size we used the web-based shiny application from Christopher Bilder available at https://www.chrisbilder.com/shiny/ under Hierarchical testing. Assuming a SARS-CoV- 2 prevalence of 4% in our query samples (see later in results section on observed test positivity rate, Figure 1 ), test sensitivity of 90%, test specificity of 98% 18 , adoption of a two stage pooling algorithm ( Figure 2 ) and a pre-specified preferred pool size range of 3-10, the algorithm calculated the optimal testing configuration was a pool size of n=6 followed by individual testing of samples in positive pools.…”
Section: Methodsmentioning
confidence: 99%